Acute effects of Ramadan intermittent fasting on sustained attention among university students in Indonesia: a field experiment - Ridwan Aji Budi Prasetyo; Fatiya Halum Husna; Yuli Rahmawati; Cantik Ummi Salsabila (International Journal of Adolescence and Youth, 2025)
Ramadan Intermittent Fasting (RIF) involves abstaining from food and drink from dawn to sunset, potentially affecting cognitive performance. This study examined whether RIF impairs sustained attention among university students. Using a repeated-measures design, 301 undergraduates (Mage = 18.51, SD = 0.67) completed the Sustained Attention to Response Test (SART). Participants were categorized as fasting (n = 205) or non-fasting (n = 96) based on self-reported fasting behaviour. Key measures, i.e. reaction time, response variability, and accuracy, were analysed using a difference-in-differences (DiD) regression model. Contrary to expectations, RIF showed no significant adverse on sustained attention, suggesting that young adults may adapt to RIF, potentially due to cognitive adaptation and the neuroprotective effects of RIF. These findings imply that attentional performance remains stable during RIF. Several limitations are acknowledged and directions for future research are proposed.